Answers

2014-11-05T19:16:05+08:00
In multiplying numbers/variables having the same base involving exponents this exponential law will apply:
a^m(a^n) = a^{m+n}
since the base x is common then you will have it as:
x^{10}(x^{12}) = x^{10+12}
x^{10+12} = x^{22}
0
do you copy it from other site? Your text seems familiar hmmmm...
there's an "insert equation" as an option in the answer box. that explains the italicization of the answer (-_-)!
oh i see.. i'm new here so i don't know anything :)
2014-11-05T23:36:34+08:00
(x^10) (x^12)=x^10+12 =x^22    by using the identity a^m x a^n = a^m+n
0